The hydrogen isotopic composition of lunar melt inclusions: An interplay of complex magmatic and secondary processes. (1st September 2020) - Stephant, A.; Anand, M.; Tartèse, R.; Zhao, X.; Degli-Alessandrini, G.; Franchi, I.A.
Abstract: Since the discovery of water (a term collectively used for the total H, OH and H2 O) in samples derived from the lunar interior, heterogeneity in both water concentration and its hydrogen isotopic ratio has been documented for various lunar phases. However, most previous studies have focused on measurements of hydrogen in apatite, which typically forms during the final stages of melt crystallisation. To better constrain the abundance and isotopic composition of water in the lunar interior, we have targeted melt inclusions (MIs), in mare basalts, that are trapped during the earliest stages of melt crystallisation. Melt inclusions are expected to have suffered minimal syn- or post-eruption modification processes, and, therefore, should provide more accurate information about the history of H in the lunar interior. Here, we report H − / 18 O − measurements as calibrated water concentrations, and hydrogen isotope ratios obtained by secondary ion mass spectrometry (SIMS) in a large set of basaltic MIs from Apollo mare basalts 10020, 10058, 12002, 12004, 12008, 12020, 12040, 14072 and 15016. Our results demonstrate that partially crystallised MIs from lunar basalts and their parental melts were influenced by a variety of processes such as hydrogen diffusion, degassing and assimilation of material affected by solar-wind implantation. Deconvolution of these processes show that lunar basaltic parental magmas were heterogeneous and had a broadly chondritic hydrogen isotopic composition with δD values varying between −200 and +200‰.